RELASI KEKUASAAN DALAM NOVEL MAUTU AR-RAJULI ALWAHIDI ALA AL-ARDHI KARYA NAWAL AS-SAâDAWI - , Dede Maemanah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Power is part of social phenomenon that straggles into every aspects of human life. Literary work as a cultural product and social expression can also contain power